2020
DOI: 10.3389/fsurg.2020.596796
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Thyroid-Like Low-Grade Nasopharyngeal Papillary Adenocarcinoma: A Case Report and Review of the Literature

Abstract: Thyroid-like low-grade nasopharyngeal papillary adenocarcinoma (TL-LGNPPA) is an extremely rare neoplasm of the nasopharynx. Accordingly, its clinical and pathological characteristics are not well-known. We report a case of TL-LGNPPA and review the relevant literature on TL-LGNPPA. A 38-year-old Japanese woman presented with a history of nasal obstruction that had persisted for 1 month after symptoms of a common cold (e.g., low-grade fever, sore throat, and fatigue). A pedunculated tumor of ∼20 mm in diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 51 publications
(92 reference statements)
2
20
0
Order By: Relevance
“…Most TL-LGNPPAs have a pedunculated and polypoid shape, and occur in any part of the nasopharynx, commonly observed on the top, lateral, and posterior walls of the nasopharynx as well as on the posterior edge of the nasal septum. [ 5 ] The mean age of patients with TL-LGNPPA is 32.3 years (range: 9–68 years), and the incidence does not differ according to sex; the tumor size ranges from 0.3 to 4.0 cm. [ 6 ] Because of its location, patients usually present with nasal obstruction and/or nasal discomfort, epistaxis, and headache.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most TL-LGNPPAs have a pedunculated and polypoid shape, and occur in any part of the nasopharynx, commonly observed on the top, lateral, and posterior walls of the nasopharynx as well as on the posterior edge of the nasal septum. [ 5 ] The mean age of patients with TL-LGNPPA is 32.3 years (range: 9–68 years), and the incidence does not differ according to sex; the tumor size ranges from 0.3 to 4.0 cm. [ 6 ] Because of its location, patients usually present with nasal obstruction and/or nasal discomfort, epistaxis, and headache.…”
Section: Discussionmentioning
confidence: 99%
“…BRAF mutations were negative in both cases, which is consistent with results reported previously in the literature. [ 5 , 7 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowgrade nasopharyngeal papillary adenocarcinoma (LGNPPA) is extremely rare among nasopharyngeal neoplasms. To our knowledge, fewer than 70 cases have been publicly reported thus far (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Because of the very low incidence of this disease, there are no guidelines or protocols developed for proper, standardized therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic resection or endoscopic resection-based therapy may be an effective method, especially for small tumors (25,26). Takakura et al reported a case of LGNPPA free of local recurrence and distant metastasis for 5 years after endoscopic resection, thus concluding that patients with LGNPPA have a very good prognosis and that complete resection with an adequate safety margin should the first-line treatment (2). In a recent single-center, retrospective study (1), 23 out of 28 patients included in the study underwent pure endoscopic treatment, with 2 cases of recurrence in the following 7-121 months of follow-up and 0 cases of recurrence or distant metastasis after endoscopic resection was applied a second time for tumor recurrence.…”
mentioning
confidence: 99%